1999
DOI: 10.1139/x99-057
|View full text |Cite
|
Sign up to set email alerts
|

Plant community responses to mechanical site preparation in northern interior British Columbia

Abstract: Ten-year response of plant communities to disk trenching, plowing, rotoclearing and windrow burning was studied on two contrasting sites to address concerns that mechanical site preparation reduces structural and species diversity. Cover and height of all species on randomly located subplots within 0.05- to 0.075-ha treatment plots were used to develop indices of volume, structural diversity, and species diversity; to ordinate the plots; and to correlate species diversity with crop-tree performance. At both si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…This does not appear to have been an important factor at the Bednesti site, however, because there was no treatment effect on comandra blister rust cumulative infection rate. A related study also reported that the treatments at Bednesti did not stimulate large increases in the herbaceous plant community (Haeussler et al 1999), which indirectly suggests little effect on G. lividum.…”
Section: Discussionmentioning
confidence: 89%
“…This does not appear to have been an important factor at the Bednesti site, however, because there was no treatment effect on comandra blister rust cumulative infection rate. A related study also reported that the treatments at Bednesti did not stimulate large increases in the herbaceous plant community (Haeussler et al 1999), which indirectly suggests little effect on G. lividum.…”
Section: Discussionmentioning
confidence: 89%
“…In boreal forests white spruce establishment is often limited by severe vegetation competition and unfavorable soil conditions, therefore treatments that affect these factors have proven to increase growth and survival of spruce (e.g., [8,26,28,48]). Both mechanical site preparation treatments and the removal of competing vegetation, by applying herbicide or fire, result in a shift in the plant community from tall shrubs (e.g., green alder and willow), as in the untreated, to mainly grasses and forbs [22,28,49]. At the Inga Lake site the treatment effect (e.g., decreased soil density and improved nutrient availability) was still significant 15 years after planting [8], but a later study at age 20 found that early microsite amelioration caused by the establishment treatments was ceasing and was having less impact on spruce growth than the negative response to competing vegetation [28].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques create a heterogeneous microtopography that could provide habitat for vascular understory plant species (Haeussler et al 1999;Ramovs and Roberts 2003), as well as hatching habitat for amphibians (Semlitsch et al 2009). …”
Section: Some Examples Of Novel Stand-level Managementmentioning
confidence: 99%